Does litter input determine carbon storage and peat organic chemistry in tropical peatlands? - Upton, Abbie; Vane, Christopher H.; Girkin, Nick; Turner, Benjamin L.; Sjögersten, Sofie (Elsevier, 2018)
Tropical peatlands hold large amounts of carbon but the influence of litter inputs and variation in peat properties with depth on carbon storage are poorly understood. Here we present a stratigraphy of peatland carbon stocks and accumulation through the peat profile in a tropical ombrotrophic wetland and assess shifts in vegetation inputs and organic matter degradation using n-alkane distributions and Rock-Eval 6 pyrolysis. Mixed forest (including canopy palms and tropical hardwood trees) contained the greatest total carbon stock in the soil (1884 Mg C ha−1), followed by Rhizophora mangle (mangrove, 1771 Mg C ha−1), Campnosperma panamensis (hardwood, 1694 Mg C ha−1) and Cyperus (sawgrass) bog plain (1488 Mg C ha−1). The long-term apparent rate of carbon accumulation, determined by 14C dating of the carbon stored in different layers in the peat profile, decreased from the edge to the interior of the peatland, with the highest accumulation rate in at the Rhizophora site (102.2 g C m−2 y−1) and the lowest in the deeper peat layers at the Cyperus site (45.6 g C m−2 y−1). High molecular weight n-alkanes dominated in surface peat in all four phasic communities, while deeper in the peat profile n-alkane profiles differed more among sites, suggesting contrasting litter inputs or decomposition environments. Deeper peat was depleted in carbohydrates and had a relatively larger thermostable C pool. Taken together our findings show (i) that different forest types hold varying C stocks and have different peat accumulation rates, even over relatively small distances, and (ii) progressive depletion of carbohydrates and thermolabile compounds with depth, despite strong variation in litter inputs throughout the peat profile.